Understanding the Low Levels of FDI Inflows to Azerbaijan in Non-Oil Sectors: Sectoral Trends and Investment Barriers - Hasanova, Aysel; Yusibova, Gulkhanim; Yusifli, Gunel (ADA University, 2025)
This capstone project examines the consistently low levels of Foreign Direct Investment (FDI) in Azerbaijan’s non-oil sectors, identifying the main structural and policy-related obstacles to diversification. The three main causes analyzed are market concentration and state dominance, regulatory and bureaucratic obstacles and infrastructure and trade-related costs. The study looks at how strong state-owned businesses, weak institutions and lack of transparency discourage investors from investing in non-oil sectors, by using official statistics, expert interviews and comparative analysis with neighboring countries like Georgia and Armenia. The paper proposes three policy options to address these causes, which include prioritizing institutional reforms over expanding incentive programs, reducing barriers to investment through regulatory reform, and Addressing infrastructure and trade related costs . Then it assesses the effectiveness of each policy option in creating an environment that is more accessible, investor-friendly and competitive. The findings highlight the necessity for a strategic change toward strengthening institutions, decreasing market concentration and systemic trade constraints to fully maximize non-oil business's potential in Azerbaijan, enhancing the regulatory framework to promote transparency and predictability in the investment sector,particularly attention is drawn to improving infrastructure quality and reducing trade costs which are important fact for making Azerbaijan a more attractive destination for foreign investors beyond the oil and gas industries.
Keywords: Foreign investments -- Government policy -- Azerbaijan; Economic diversification -- Azerbaijan; Non-oil sector -- Economic policy; Infrastructure (Economics) -- Government policy; Institutional reform -- Azerbaijan; Public and International Affairs